Studies on the life cycle of Haplorchis pumilio (Looss, 1896) (Trematoda: Heterophyidae) in Venezuela - Díaz, Marcos; Hernandez, Luis Elena; Bashirullah, Abul (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
The life cycle of Haplorchis pumilio was studied from redia to adult under natural and experimental conditions. The precercarial stage (redia) was found in the digestive gland of Melanoides tuberculata (natural infection), collected from Aguasanta, Sucre State, Venezuela. Metacercariae were located in muscular tissues, under the scale of the caudal fin of Rivulus harti (natural infection). Metacercariae were supplied to ducks, chickens, rats and mice, and 3 days after infection, 28 adult H. pumilio were recovered from the small intestine of the ducks. R. harti, Poecilia reticulata, Oreochromis mossambicus and Astyanax spp. were exposed experimentally to cercariae emitted by M. tuberculata: only R. harti was found infected. The 30 days old metacercariae were experimentally supplied to ducks and chickens, and a total of 32 adult trematodes were found 3 days after inoculation of 20 metacercarias to each duck. Butorides striatus was found to be the natural final host of H pumilio. Morphometric characteristics of adult H. pumilio from both natural and experimental hosts differ from adults described previously. These differences may be due to differences in host and geographical variations. H. pumilio in R. harti and B. striatus report new host records.